Analysis of the correlation and influencing factors between delirium, sleep, self-efficacy, anxiety, and depression in patients with traumatic brain injury: a cohort study - Fu, Zhongmin; Miao, Xiaoju; Luo, Xian; Yuan, Lili; Xie, Yan; Huang, Shiming (Frontiers in Neuroscience, 2024)
BackgroundPatients with traumatic brain injury (TBI) often experience post-injury anxiety and depression, which can persist over time. However, the relationships between anxiety and depression in TBI patients and delirium, sleep quality, self-efficacy, and serum inflammatory markers require further investigation.ObjectiveThis study aims to explore the associations of delirium, sleep quality, self-efficacy, and serum inflammatory markers with anxiety and depression in TBI patients, and to examine potential influencing factors.MethodsWe conducted a cohort study involving 127 patients with TBI. Delirium was assessed using the Confusion Assessment Method (CAM) and CAM-ICU, while anxiety, depression, sleep quality, self-efficacy, and pain were evaluated using the appropriate tools, respectively. Serum inflammatory markers (CRP, TNF-α, IL-6) were collected within 1 day post-injury. Generalized estimating equations (GEE) were used to analyze the relationships between delirium, sleep, self-efficacy, and anxiety/depression.ResultsThe study identified 56 patients with delirium. Patients with delirium differed significantly from those without delirium in age, TBI classification, sleep duration, CRP levels, TNF-α levels, pain, self-efficacy, and insomnia (P < 0.05). The GEE analysis revealed that delirium, CRP levels, self-efficacy, underlying diseases, insomnia, TBI classification, age, and sleep duration were associated with anxiety symptoms in TBI patients at 6 months post-discharge (P < 0.05). Depression in TBI patients at 6 months post-discharge was not associated with delirium or insomnia but correlated with CRP levels, TBI classification, and self-efficacy (P < 0.05).ConclusionTBI patients who experience delirium, insomnia, and low self-efficacy during the acute phase are likely to exhibit more anxiety at the 6-month follow-up. Depression in TBI patients is not associated with delirium or insomnia but is negatively correlated with self-efficacy. CRP levels post-TBI may serve as a biomarker to identify patients at risk of emotional symptoms and potentially accelerate patient recovery.